2022
DOI: 10.3389/fcell.2022.775417
|View full text |Cite
|
Sign up to set email alerts
|

New Prognostic Gene Signature and Immune Escape Mechanisms of Bladder Cancer

Abstract: Background: The immune microenvironment profoundly affects tumor prognosis and therapy. The present study aimed to reveal potential immune escape mechanisms and construct a novel prognostic signature via systematic bioinformatic analysis of the bladder cancer (BLCA) immune microenvironment.Patients and Methods: The transcriptomic data and clinicopathological information for patients with BLCA were obtained from The Cancer Genome Atlas (TCGA). Consensus clustering analysis based on the CIBERSORT and ESTIMATE al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(49 reference statements)
0
3
0
1
Order By: Relevance
“…Therefore, some studies have revealed that IBSP promotes bone metastasis of tumor cells in BRCA ( 9 ), PRAD ( 27 ), and non-small cell lung cancer ( 21 ). Recently, with the development of bioinformatics, some studies demonstrated that the expression of IBSP is upregulated in epithelial tumors such as laryngeal cancer ( 28 ) and BLCA ( 29 ), which is highly correlated with a poor prognosis. For malignant tumors of non-epithelial origin, such as GBM, IBSP can also promote tumor cell proliferation and migration ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some studies have revealed that IBSP promotes bone metastasis of tumor cells in BRCA ( 9 ), PRAD ( 27 ), and non-small cell lung cancer ( 21 ). Recently, with the development of bioinformatics, some studies demonstrated that the expression of IBSP is upregulated in epithelial tumors such as laryngeal cancer ( 28 ) and BLCA ( 29 ), which is highly correlated with a poor prognosis. For malignant tumors of non-epithelial origin, such as GBM, IBSP can also promote tumor cell proliferation and migration ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…基于11个与膀胱癌预后相关的ICRG建立膀胱癌预后评分方程,回归分析显示该风险评分是膀胱癌患者预后的独立影响因素。结合临床特征构建的列线图也展示出对膀胱癌患者预后较好的预测价值。与其他基因集构建的膀胱癌预后风险评估模型比较,本研究构建的模型在预测膀胱癌患者5年存活率方面有着更高的效能 [ 18 52 ] 。此外,相比Liang等 [ 53 ] 构建的15个基因的模型,本研究构建的模型纳入的基因数较少,检验难度小,便于应用于临床。本研究还发现风险评分与肿瘤免疫细胞浸润密切相关。浆细胞、活化NK细胞、静息肥大细胞免疫浸润水平在低风险组患者中显著上调,而在高风险组中M2型巨噬细胞浸润水平明显高于低风险组,提示高风险组患者存在免疫抑制微环境。上述研究结果可以为膀胱癌患者的免疫治疗提供一定的参考。…”
Section: 讨论unclassified
“…However, the 5-year survival rate and median survival of bladder cancer are still difficult to achieve satisfactory results ( 6 - 8 ). With the development of bioinformatics technology, more and more literature shows that genes can be used as biomarkers for prognosis prediction of bladder cancer ( 9 - 13 ).…”
Section: Introductionmentioning
confidence: 99%